Case Report: Anencephaly in an Unidentified Baby - Mandasari, Safira (Syntax Literate, 2024)
Anencephaly is a congenital disorder affecting the central nervous system, characterized by the absence of a major portion of the brain, skull, and scalp, with an estimated prevalence of 0.5–2 per 1,000 births globally. This condition is a subset of Neural Tube Defects (NTDs), which affect approximately 300,000 newborns annually. This study aims to investigate the pathological and forensic aspects of a case of anencephaly in a female infant found deceased in Lingsar, West Lombok, on June 23, 2023. The methods employed case study included external and internal examinations to identify the structural abnormalities and potential cause of death. The external examination revealed open wounds on several parts of the body, and discoloration of the chest and abdominal cavities. Internal examination confirmed the absence of brain tissue, consistent with anencephaly. The findings indicate that the cause of death was directly attributed to the severe congenital anomaly, with no evidence of external factors contributing to mortality. The study concludes that anencephaly, while rare, remains a significant congenital disorder with profound implications for prenatal care and early detection. This case emphasizes the necessity of improving maternal nutrition, particularly folic acid supplementation, as a preventive strategy to reduce the incidence of NTDs. The findings also underscore the importance of interdisciplinary collaboration in handling forensic and medical investigations of congenital disorders, aiding in better understanding and management of similar cases in the future.